The Effectiveness of Using YouTube on Fireman Sam Channel To Improve Vocabulary Mastery in Teaching Listening - Ria Dewi Hudayani Sugara; Ria Saparianingsih; Azkia Fathia Lidinillah (Scope : Journal of English Language Teaching, 2023)
This research is about the use of YouTube on the Fireman Sam channel to improve vocabulary skills in teaching listening.  The objectives of this research are: 1) To identify the Firemans’ Sam channel improve vocabulary mastery in teaching listening; 2) To identify Firemans’ Sam Channel is effective in vocabulary mastery. This research method was a quasi-experimental in which the data collection used two tests, pretest and posttest, both of which were listening tests. Then the data were analyzed using t-test to find out whether there is a significant difference after being given treatment. The finding of this research before getting the treatment the sample got the mean of each test in pre-test is 43,33. After being seen from the t-test that there is a significant value of 0.000 because it is less than 0.05, the researchers assume that the use of YouTube on Fireman Sam's channel improves vocabulary skills that will be effective in teaching students' listening and can be used as an alternative media in teaching listening.